Innovative tax administration tools in Russia - N. G. Мorozova; Zh. M. Korzovatykh (Вестник университета)
The article examines the current system of tax administration in Russia and its innovative tools, actively developed and implemented in the context of the digital technologies’ rapid development and the transformation of the control and supervisory state activities. The purpose of the study is to determine the main directions for improving tax administration in the Russian Federation. The research method was the content analysis of scientific publications on tax administration and control in modern conditions. The paper solves the tasks of the tax authorities’ activities effectiveness evaluating, identifying problems in the application of tax administration tools and ways to solve them. The use of information technologies makes it possible to expand the tax administration possibilities, as the main element in the practical implementation of tax policy, which directly affects the tax control effectiveness. The scientific value of the article lies in determining the directions for further development of tax administration tools aimed at increasing the tax authorities’ efficiency and the service quality for economic entities in digital interaction between the state represented by tax authorities and taxpayers.